1982
DOI: 10.1159/000179507
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Placenta Levels of Ethynylestradiol in Presence of Ethynodiol Diacetate after Oral Administration

Abstract: The ethynylestradiol concentration – in the presence of ethynodiol diacetate – in serum after oral administration was measured by a rapid radioimmunoassay method developed by the authors. It was found that the peak level was reached 1 h after administration, and even after 12 h a significant amount of free ethynylestradiol was present in the serum. The transfer of ethynylestradiol into the placenta was also studied in subjects who were 10–12 weeks pregnant. Placenta/serum quotients were calculated for the ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…On examination of the appearance of sul famethoxazole and trimethoprim in the sali va, Eat man et al [1] found a phase shift of only 1/2-1 h. These drugs, however, are of a markedly polar nature, in contrast, to the TIME AFTER ORAL ADMINISTRATION On the other hand, corresponding to our previous finding that the observable percent age of the dose found in the free state in the serum decreases with increasing dose [7], the excretion of ethynylestradiol will also quicken when the dose is raised. This makes it possible to observe, at an earlier stage, a significant increase in the concentration in the saliva.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…On examination of the appearance of sul famethoxazole and trimethoprim in the sali va, Eat man et al [1] found a phase shift of only 1/2-1 h. These drugs, however, are of a markedly polar nature, in contrast, to the TIME AFTER ORAL ADMINISTRATION On the other hand, corresponding to our previous finding that the observable percent age of the dose found in the free state in the serum decreases with increasing dose [7], the excretion of ethynylestradiol will also quicken when the dose is raised. This makes it possible to observe, at an earlier stage, a significant increase in the concentration in the saliva.…”
Section: Discussionsupporting
confidence: 63%
“…Previously, we examined the placenta/serum quotient [7], and for comparison purposcs it seemed worthwhile to determine the saliva/serum quotient, too. Figure 1 shows that for an oral ethynylestradiol dose of 0.05 mg this was only 0.27 2 h after adminis tration, 0.76 after 4 h, 0.53 after 6 h and about 0.40 after 12 h. Thus, determination of the relation between the contents of ethynyl estradiol in serum and saliva is possible only when the samples to be analyzed have been taken at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this rea son, the purpose of our study was to deter mine experimentally the ethynyl estradiol concentration in the cervical mucus, for this is the most frequent estrogen component of oral contraceptives. The ethynyl estradiol contents of the serum and placenta have already been studied [7],…”
Section: Introductionmentioning
confidence: 99%